Cosmological screening and the phantom braneworld model - Sourav Bhattacharya; Stefanos R. Kousvos; Stylianos Romanopoulos; Theodore N. Tomaras (European Physical Journal C: Particles and Fields, 2018)
Abstract The scalar and vector cosmological perturbations at all length scales of our Universe are studied in the framework of the phantom braneworld model. The model is characterized by the parameter $$Ω _M\equiv M^3/2m^2H_0$$ ΩM≡M3/2m2H0 , with M and m the five- and four-dimensional Planck scales, respectively, and $$H_0$$ H0 the Hubble parameter today, while $$Ω _M→ 0$$ ΩM→0 recovers the $$Λ \mathrm CDM$$ ΛCDM model. Ignoring the backreaction due to the peculiar velocities and also the bulk cosmological constant, allows the explicit computation of the gravitational potentials, $$Φ $$ Φ and $$Ψ $$ Ψ . They exhibit exponentially decreasing screening behaviour characterized by a screening length which is a function of the quasidensity parameter $$ Ω _M$$ ΩM .